2017
DOI: 10.1021/acs.joc.7b00861
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (1 → 2)-S-Linked Saccharides and S-Linked Glycoconjugates via a Palladium-G3-XantPhos Precatalyst Catalysis

Abstract: Buchwald-Hartwig-Migita cross-coupling of 1-thiosugars with 2-iodoglycals has been accomplished under mild and operationally simple reaction conditions through the use of Pd-G3 XantPhos palladacycle precatalyst. This new methodology has been successfully applied to a variety of α- or β-mono-, di-, and polythiosugar derivatives to synthesize efficiently a series of (1 → 2)-S-linked thiosaccharides and S-linked glycoconjugates, which are difficult to synthesize by classical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
0
35
0
1
Order By: Relevance
“…The reaction is versatile (various aryl, akenyl, and alkynyl halides can be used), tolerates several functional groups (eg, –Br, –OTs, –OH, –CN, –CO 2 Me, –CONR 2 , C(Me)=NNHTs) and it is reproducible up to a multigram scale. The scope was then expanded to (1→2)‐ S ‐linked saccharides and S ‐linked glycoconjugates . The same method was also applied to heteroaryl bis‐glycosides, where N ‐glycosyl quinolin‐2‐ones (general structure 170 reported in Figure ) where a glycosyl unit is attached to a quinolin‐2‐one core (one of the most important heterocycle in medicinal chemistry) …”
Section: Exocyclic Oxygen Replacementmentioning
confidence: 99%
“…The reaction is versatile (various aryl, akenyl, and alkynyl halides can be used), tolerates several functional groups (eg, –Br, –OTs, –OH, –CN, –CO 2 Me, –CONR 2 , C(Me)=NNHTs) and it is reproducible up to a multigram scale. The scope was then expanded to (1→2)‐ S ‐linked saccharides and S ‐linked glycoconjugates . The same method was also applied to heteroaryl bis‐glycosides, where N ‐glycosyl quinolin‐2‐ones (general structure 170 reported in Figure ) where a glycosyl unit is attached to a quinolin‐2‐one core (one of the most important heterocycle in medicinal chemistry) …”
Section: Exocyclic Oxygen Replacementmentioning
confidence: 99%
“…Samir Messaoudi and his group [26] used 2-iodoglycals as coupling partners for the synthesis of thioglycosides (Scheme 12). They have used both αand β-glycosyl thiols in the Pd-catalyzed Buchwald-Hartwig-Migita cross-coupling approach under mild reaction conditions.…”
Section: Coupling Of Glycosyl Thiols With 2-iodo Glycalsmentioning
confidence: 99%
“…In later reports Messaoudi and co-authors showed largely the potential application of this protocol. The authors started by highlighting the synthesis of (1→2)-S-Linked saccharides and S-linked glycoconjugates via a Pd-G3-XantPhos precatalyst catalysis [42] . This efficient methods allowed successfully the synthesis of various (1→2)-S-linked saccharides via a palladium precatalyst-catalyzed coupling of α-or β-mono-, di-, and polythiosugar derivatives with 2-iodoglycals.…”
Section: Scheme 14mentioning
confidence: 99%